Tafsir Ayat Al Quran Tentang Penistaan Agama - Aszmi Farida; Randy Maulana; Akenada Putri Millian; Jendri Jendri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Complex social problems, such as blasphemy, often arise as a result of social plurality. Time pressure can make the legal system no longer subjective in such situations. If protests continue, the punishment imposed on those deemed to have committed blasphemy will be increasingly severe. Cases of blasphemy have increased in recent times. When some people easily say that such an attitude is blasphemy, the author was moved to investigate and analyze the verses in the Qur'an related to blasphemy using their understanding of classical, medieval, and contemporary interpretations. This qualitative research uses a comparative approach. The author uses Tafsir Jami' al-Bayan'an Ta'wil ai al-Qur'an, Tafsir al-Jami' li Ahkam Al-Qur'an, and Tafsir al-Munir from Wahbah az-Zuhailîy as primary data sources, and books related to blasphemy are used as secondary data sources. The data were studied using deductive-comparative methods. This study shows that some words are involved in the discussion of blasphemy when compared to its general meaning, although the Qur'an does not mention the word